USE OF HYDROXYLAMINE) NH2OH ( TO INDUCE GENETIC CHANGES IN SOME LABORATORY AND FIELD TRAITS IN BLACK BEAN PLANT PHASEOLUS VULGARIS - Dr. Asseel M.M. Habh; Baan Munim Twaij; Rasha Mohamed Sajet Al-Oqaili; Hasan abdulhusein hafeadh (Scholar Express Journals, 2023)
The study included the creation of variations using the chemical mutagenic hydroxylamine) NH2OH (in four concentrations 0, 0.5 ,1, 1.5 M of black bean plant Phaseolus vulgaris . If the seeds were soaked in the above concentrations for a different period of time15, 24, 32H. The seeds treated with the mutagen were divided into two parts: the first part was sown in Petri dishes, while the second part was planted in the field according to the randomized complete block design. Germination percentage, germination speed/day, and root length were calculated in the laboratory. When the plants reached the stage of maturity, random samples were taken from the plants to study the effect of hydroxylamine NH2OH on the yield components, namely the number of pods, the length of the pod, and the number of seeds / pod. The results showed that hydroxylamineNH2OH had a significant effect in reducing the percentage of germination, germination speed / day, average root length, average pod length, number of pods / plant and number of seeds / pod at high concentrations. It turns out that the best concentration of the mutagen) 1M( to cause beneficial changes can be selected to increase the yield of the plant
Keywords: legumes; Phaseolus vulgaris; seeds